Mental health risks in pregnancy and early parenthood among male and female parents following unintended pregnancy or fertility treatment: a cross-sectional observational study - Naoki Mizunuma; Keiko Yamada; Takashi Kimura; Yutaka Ueda; Takashi Takeda; Takahiro Tabuchi; Kunihiko Kurosaki (BMC Pregnancy and Childbirth)
Abstract Background Unintended pregnancy at higher risk of perinatal mood disorders; however, concurrent factors such as socioeconomic conditions may be more critical to mental health than pregnancy intention. Mental health risks among individuals undergoing fertility treatment are inconsistent. We investigated mental health risks during pregnancy and parenthood in parents who conceived unintentionally or through fertility treatment compared to those who conceived naturally and intentionally. Methods We conducted a web-based study with 10,000 adults ≥ 18 years old, either pregnant or with a child aged < 2 years. Male and female respondents weren’t couples. We analyzed 1711 men and 7265 women, after filtering out invalid responses. We used a questionnaire including conception methods (e.g., naturally conceived intended/unintended pregnancies, fertility treatment such as scheduled intercourse or ovulation inducers [SI/OI], intrauterine insemination [IUI], and in-vitro fertilization or intracytoplasmic sperm injection [IVF/ICSI]) and mental health risks (e.g., psychological distress, chronic pain, death fantasies). Using a modified Poisson regression, we estimated relative risks (RR [CI]) for mental health risks compared to those with intended pregnancies. Results Unintended pregnancy showed higher mental health risks during pregnancy in both genders, with women having significantly higher psychological distress, chronic pain, and death fantasies (RR 1.63 [1.05–2.54], RR 1.63 [1.14–2.33], and RR 2.18 [1.50–3.18], respectively). Women’s death fantasies risk remained high in parenthood: RR 1.40 (1.17–1.67). In relation to fertility treatments, men using SI/OI during their partner’s pregnancy showed higher mental health risks, especially for chronic pain (RR 1.75 [1.01–3.05]). Men who underwent IUI showed higher mental health risks during parenthood, notably death fantasies (RR 2.41 [1.13–5.17]). Pregnant women using SI/OI experienced higher mental health risks, with a significant risk of chronic pain (RR 1.63 [1.14–2.33]). Pregnant women using IVF/ICSI had a significantly lower risk of chronic pain (RR 0.44 [0.22–0.87]), but women who used IVF/ICSI had a significantly higher risk of death fantasies during parenthood (RR 1.40 [1.04–1.88]). Conclusions Mental health risks vary by parenting stage (pregnancy or early parenthood) and gender, especially for those who conceived unintentionally or through fertility treatment. Both stages require adaptable mental health support for all parents. Trial registration N/A (non-interventional study).